Fishing up the Food Web?: 12,000 Years of Maritime Subsistence and Adaptive Adjustments on California's Channel Islands - Erlandson, Jon M.; Rick, Torben C.; Braje, Todd J. (Pacific Science, 2009)
Archaeologists working on California's northern Channel Islands have produced an essentially continuous record of Native American fishing and nearshore ecological changes spanning die last 12,000 years. To search for evidence of Pauly's "fishing down the foodweb" pattern typical of recent historical fisheries, we analyzed variation in the dietary importance of major marine faunal classes (shellfish, fish, marine mammals) on the islands through time. Faunal data suggest that the Island Chumash and their predecessors focused primarily on low-trophic-level shellfish during the Early and Middle Holocene, before shifting their economic focus to finfish and pinnipeds during the Late Holocene. Replicated in faunal sequences from the adjacent mainland, this trans-Holocene pattern suggests that Native Americans fished Lip the food web, a strategy that may have been more sustainable and had fewer ecological repercussions. Emerging technological data suggest, however, that some of the earliest Channel Islanders focused more heavily on higher-trophic-level animals, including marine mammals, seabirds, and waterfowl. These data emphasize the differences between the primarily subsistence-based foraging strategies of ancient Channel Islanders and the globalized market-based fisheries of modern and historic times, with important implications for understanding the long-term evolution and historical ecology of marine ecosystems.
id: 2059; PT: J; UT: WOS:000270849400011